Petrology, geochemistry and thermobarometry of the northern area of the Flamenco pluton, Coastal Range batholith, northern Chile. A thermal approach to the emplacement processes in the Jurassic andean batholiths. (April 2016) - Rodríguez, Natalia; Díaz-Alvarado, Juan; Rodríguez, Carmen; Riveros, Karl; Fuentes, Paulina
Abstract: The Flamenco pluton is part of a N–S alignment of Late Triassic to Early Jurassic intrusive belt comprising the westernmost part of the Coastal Range batholith in northern Chile. The Jurassic-Cretaceous voluminous magmatism related to subduction in the western active continental margin of Gondwana is emplaced in the predominantly metasedimentary Paleozoic host-rocks of the Las Tórtolas formation, which in the northern area of the Flamenco pluton present an intense deformation, including the Chañaral mélange. Geochemically, the Flamenco pluton shows a wide compositional variability (SiO2 between 48wt % and 67wt %). Gabbros, Qtz-diorites and tonalites, mesocratic and leucocratic granodiorites are classified as calc-alkaline, calcic, magnesian and metaluminous magmatism. Flamenco granitoids define cotectic linear evolution trends, typical of magmatic fractionation processes. Geochemical trends are consistent with magmas evolved from undersaturated and low-pressure melts, even though the absence of transitional contacts between intrusive units precludes in-situ fractionation. Although some granodioritic samples show crossed geochemical trends that point to the compositional field of metasediments, and large euhedral prismatic pinnite-biotite crystals, typical Crd pseudomorph, are observed in contact magmatic facies, geochemical assimilation processes are short range, and the occurrence of host-rocks xenoliths is limited to a few meters from the pluton contact. A thermal approach to the emplacement process has been constrained through the thermobarometric results and a 2D thermo-numerical model of the contact aureole. Some Qtz-diorites and granodiorites located in the north area of the pluton exhibit granulitic textures as Hbl-Pl-Qtz triple junctions, poikiloblastic Kfs and Qtz recrystallization. The Hbl–Pl pairs have been used for the thermobarometric study of this metamorphic process, resulting granoblastic equilibrium temperatures between 770 and 790 °C, whereas Hbl–Pl pairs in domains that preserve the original igneous textures yield temperatures above 820 °C. This is characteristic of self-granulitization processes during the sequential emplacement of composite batholiths. In addition, the thermal modeling was used in order to compare the expected and observed thermal contact aureole of the intrusive body. Model P-T conditions have been established between 3 and 4 kbars (extracted from the thermobarometric results), and temperatures between 1159 °C ( liquidus temperature for a tonalitic composition) and 992 °C (fixed at the rheological threshold of a 50% crystal fraction). The thermal modeling estimates a homogeneous contact aureole, where the established temperatures for the melting reactions in the host-rocks are located at distances between 200 and 650 m from the magma chamber boundary, whereas the temperatures for Crd stabilization extend 1500 m far from the contact in the case of the emplacement at liquidus temperatures and 4 kbars. According to field observations, the contact aureole presents a scarce development in the northern area of the Flamenco pluton, with few migmatite outcrops and less than 1 Km in thickness for Crd-schists. However, in the southern contact, partially melted rocks are described at distances up to 2 km from the Flamenco pluton boundary. The processes of self-granulitization and the differences between the observed and calculated (by the thermal modeling of one single pulse) contact aureole suggests a process of incremental emplacement for the Flamenco pluton, by accretion of magmatic pulses from north to south (in its current position), where the thermal maturity reached through the repeated magmatic intrusion generates a more extensive area of high-grade metamorphism. Graphical abstract: Highlights: Early Jurassic Flamenco pluton included in the Coastal Range batholith. Gabbros, Qtz-diorites to granodiorites calc-alkaline association. Auto-granulitization during the emplacement process. Homogeneous calculated vs. heterogeneous observed thermal aureole. Incremental emplacement by accretion of magmatic pulses.